2006
DOI: 10.1016/j.ejcts.2005.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Indexed effective orifice area after mechanical aortic valve replacement does not affect left ventricular mass regression in elderly

Abstract: The major finding of our study is that patient-prosthesis mismatch does not affect left ventricular mass regression in patients older than 65 with pure aortic stenosis who underwent mechanical aortic valve replacement. In older patients with low cardiac output requirements, even a small change in the valve effective orifice area after aortic valve replacement with modern efficient mechanical prosthesis, will result in a marked reduction of pressure gradient and this will be associated with a significant regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…18 Regarding the relationship between regression of the LVMI and PPM, Roscitano et al showed that PPM did not affect regression of the LVMI in patients >65 years. 19 Aoyagi et al showed that LVMI reduction in patients with small valves (19 or 21 mm) was not different from that in patients with large valves (23 or 25 mm). 20 In the present study, follow-up echocardiography showed a significant decrease in the LVMI, >20% reduction from the preoperative value, regardless of PPM at discharge.…”
Section: Discussionmentioning
confidence: 99%
“…18 Regarding the relationship between regression of the LVMI and PPM, Roscitano et al showed that PPM did not affect regression of the LVMI in patients >65 years. 19 Aoyagi et al showed that LVMI reduction in patients with small valves (19 or 21 mm) was not different from that in patients with large valves (23 or 25 mm). 20 In the present study, follow-up echocardiography showed a significant decrease in the LVMI, >20% reduction from the preoperative value, regardless of PPM at discharge.…”
Section: Discussionmentioning
confidence: 99%
“…16 Echocardiographic analysis also showed that PPM did not affect LVM regression rate after AVR in the midterm. 7,12 In this study, although all PPM(+) patients had moderate PPM (i-EOA ≥ 0.65), there was no signifi cant Left ventricular mass (LVM) index, from analysis by echocardiography, was signifi cantly reduced after AVR in both groups. Furthermore, there was no signifi cant difference in the postoperative LVM index between groups impact on operative mortality, midterm outcome, or LVM regression rate in the PPM(+) group.…”
Section: Discussionmentioning
confidence: 55%
“…Some authors have stated that the advantage of a mechanical valve in the elderly is a signifi cant LVM regression rate, low long-term mortality, and a low incidence of major adverse cardiac events after AVR compared with bioprostheses. 7,8 On the other hand, bioprostheses have come into common use for elderly people over 60-65 years during the last decade. Kulik and his colleagues suggested that it is diffi cult to lower the usual cutoff age for implantation of a bioprosthesis below 65 years because more reoperations are required in patients implanted with bioprostheses than in those with mechanical valves when they are between 50 and 65 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the association between LVMI and PPM, Roscitano et al [9] have shown that PPM did not affect the regression of LVMI in patients >65 years old. Some studies have shown that PPM is a strong and independent predictor of mortality among patients with AVR, [10,11] whereas others have shown no effects [12,13].…”
Section: Discussionmentioning
confidence: 99%